Konstruksi Ideologi Pendidikan dalam Lanskap Linguistik Virtual Media Sosial Instagram Badan Gizi Nasional: Analisis Wacana Kritis terhadap Praktik Diskursif dan Praktik Sosial - Wijaya, Tubagus; Savitri, Agusniar Dian; Yuniseffendri, Yuniseffendri (Lembaga Teewan Journal Solutions, 2026)
This study aims to uncover the construction of educational ideology in the virtual linguistic landscape of the National Nutrition Agency's official Instagram account through the Free Nutritious Meal Program (MBG) content. A qualitative approach with a critical paradigm was employed using Norman Fairclough's Critical Discourse Analysis model. The data consist of 42 Instagram posts from January–May 2026, including infographics, photos, videos, captions, hashtags, and institutional symbols. Data were collected through digital documentation and virtual observation. The findings reveal that MBG discourse represents nutrition as an educational investment. In the text dimension, diction such as golden generation, balanced nutrition, and children's rights construct moral legitimacy. In discursive practice, Instagram integrates information, education, and emotional narratives. In social practice, BGN discourse naturalizes MBG as a welfare program and human resource development strategy toward Golden Indonesia 2045. This study confirms that government social media serves as an ideological space shaping public awareness through language, visuals, symbols, and national narratives.